(untitled) (The Research of Medical Science Review, 2025)
Background: ST-elevation myocardial infarction (STEMI) significantly compromises left ventricular function, contributing to long-term morbidity and mortality. Early revascularization with primary percutaneous coronary intervention (PCI) plays a crucial role in preserving myocardial function and improving outcomes. Objective: To assess the improvement in left ventricular ejection fraction (LVEF) three months after primary percutaneous coronary intervention (PCI) in patients presenting with ST-elevation myocardial Infarction and Left Ventricular Dysfunction. Methodology: A descriptive cross-sectional study was conducted on 199 patients presenting with STEMI who underwent primary PCI. Baseline clinical, demographic, and angiographic data were recorded. Left ventricular ejection fraction (LVEF) was measured at admission and reassessed after 3 months to evaluate improvement. Associations between LVEF recovery and various clinical factors were statistically analyzed. All data were analyzed using SPSS version 26. Continuous variables such as age, height, weight, BMI, door-to-balloon time, and LVEF values were expressed as means ± standard deviations. Categorical variables such as gender, presence of comorbidities, and STEMI type were presented as frequencies and percentages. Inferential statistics were applied to determine associations between clinical variables and LVEF improvement. The chi-square test was used for categorical data, and a p-value of <0.05 was considered statistically significant. Result: Out of 199 STEMI patients, 75.3% showed ≥10% improvement in LVEF at 3 months. Anterior wall MI (69.8%) and LAD involvement (69.8%) were the most common. LVEF improvement was significantly associated with the absence of hypertension (p=0.015), anterior STEMI (p=0.0001), and absence of no-reflow phenomenon (p=0.0001). Diabetes and smoking showed no significant association. Conclusion: Patients who had primary PCI for STEMI experience meaningful improvement in left ventricular ejection fraction (LVEF) within three months of intervention. The most notable predictors of poor LVEF recovery were hypertension, anterior STEMI, and the presence of no-reflow or distal embolism. These findings underscore the critical importance of early identification and aggressive management of high-risk STEMI patients, particularly those with anterior infarctions or hemodynamic instability post-PCI.